Self-Reflection and Insight pada Mahasiswa Kedokteran dan Hubungannya dengan Persepsi terhadap Perilaku Profesional - Shulhana Mokhtar; Ova Emilia; Efrayim Suryadi (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2013)
Background: In term of health service duty, physicians unprofessional behavior, than their lack of knowledge or skills, are more likely to cause some problem. The issues of professionalism can be identified when student are still in the process of education. There are several things associated with the development of professionalism, such as self-reflection and the ability to understand (insight) the incidents around them in this study professional behavior was mainly connected with responsibility. This study aimed to examined the relationships between UMI medical students (SRI) and perception of professionalism (responsibility)Method: It is a quantitative study using cross sectional approach. The participants were UMI students of batch 2009-2011 who are still studying at the university data were obtained from the questionnaires SRI scale and perceptions scale. Descriptive statistics, t-test and ANOVA-test and Pearson correlation test were used to analyze the data.Results: In general, students SRI score were LOW (M=2,46), as well as students’ perceptions of responsible behavior (M= 2,25). Based on students characteristics, significant difference in SRI was only found in the high school of origin (p = 0,043) and in the perception was found in father’s occupation (p = 0,018). Correlation analysis found a significant relationship between SRI and perceptions of professionalism (p = 0,0001).Conclusion: Self-reflection and insight of UMI medical students were still low and they were aligned with students’ perceptions of professional conduct (responsibility) which were also low. These values varied by students characteristics but for all intents and purposes, the differences were not significant.